We decide! : theories and cases in participatory democracy - Menser, Michael (Global ethics and politics., 2018)
"Participatory democracy calls for the creation and proliferation of practices and institutions that enable individuals and groups to better determine the conditions in which they act and relate to others. Michael Menser's timely book We Decide! is arguably the most comprehensive treatment of participatory democracy. He explains the three waves of participatory democracy theory to show that this movement is attentive to the mechanics of contemporary political practices. Menser also outlines "maximal democracy," his own view of participatory democracy that expands people's abilities to shape their own lives, reduce inequality, and promote solidarity. We Decide! draws on liberal, feminist, anarchist, and environmental justice philosophies as well as in-depth case studies of Spanish factory workers, Japanese housewives, and Brazilian socialists to show that participatory democracy actually works. Menser concludes his study by presenting a reconstructed version of the state that is shaped not by corporations but by inclusive communities driven by municipal workers, elected officials, and ordinary citizens working together. In this era of Bernie Sanders and Donald Trump, the participatory democracy proposed in We Decide! is more significant than ever"--